Implementation Of A Problem Based Learning Model With The Assistance Of Ai To Improve Students' Critical Thinking Abilities And Creativity - Novtiana, Rizcha; Harmanto, Harmanto; Nuaimah, Sulasun (Jurnal Ilmu Sosial Mamangan, 2024)
This research explores the effectiveness of the problem based learning (PBL) learning model with the help of artificial intelligence (AI) in improving students' critical thinking abilities and creativity. Using a qualitative literature review approach, data was obtained from academic databases and online libraries with selection according to inclusion criteria. Descriptive analysis was carried out to understand the main findings regarding the implementation of the PBL model with AI, its impact on students' critical thinking abilities and creativity, as well as the factors that influence the success of its implementation. The results of the literature analysis provide insight into the advantages, weaknesses, and potential for further development of the learning approaches studied. It is hoped that this research will contribute to the development of learning methods that strengthen students' critical thinking abilities and creativity, as well as becoming a guide for educational practitioners and policy developers to improve the quality of learning in various educational institutions